Polyphenols and extracts from Zingiber roseum (Roxb.) Roscoe leaf mitigate pain, inflammation and pyrexia by inhibiting cyclooxygenase-2: an in vivo and in silico studies - Shakhawat Ahmed; Khondoker Shahin Ahmed; Md. Naiemur Rahman; Hemayet Hossain; Aixia Han; Peiwu Geng; A. F. M. Shahid Ud Daula; Abdullah Al Mamun (Frontiers Media S.A., 2024)
Zingiber roseum (Roxb.) Roscoe, a perennial herb from the Zingiberaceae family, has a long history of traditional use in the treatment of several ailments including pain, inflammation, fever, cough, arthritis, skin diseases, and liver infections. This study sought to confirm the efficacy of Zingiber roseum (Roxb.) Roscoe leaves methanol extract (ZrlME) as reported in traditional usage by evaluating its analgesic, anti-inflammatory, and antipyretic capabilities. In addition, in silico molecular docking of the metabolites identified in ZrlME was studied to verify the experimental outcomes. ZrlME demonstrated strong dose-dependent analgesic efficacy against all analgesic tests. ZrlME (400 mg/kg) showed higher anti-inflammatory activity than the standard in the carrageenan-induced paw edema test model. A significant reduction of rectal temperature (3.97°F↓) was also recorded at the same dose of ZrLME after 24 h of treatment. Seven polyphenolic metabolites were identified and quantified by HPLC-DAD analysis, including 3, 4- dihydroxy benzoic acid, (-) epicatechin, rutin hydrate, p-coumaric acid, trans-ferulic acid, rosmarinic acid, and myricetin. Strong binding affinities (ranges from −5.8 to −8.5 Kcal/mol) between the aforesaid polyphenols and cyclooxygenase-2 were discovered. Moreover, molecular dynamics simulations (MDS) demonstrated that these polyphenols exhibit significant COX-2 inhibitory activity due to their high stability in the COX-2 active site. In computational prediction, the polyphenols were also found to be nontoxic, and a variety of biological activities, such as antioxidant, analgesic, anti-inflammatory, antipyretic, and hepatoprotective, were observed. The results of this study revealed that ZrlME possesses notable analgesic, anti-inflammatory, and antipyretic properties.